Islamic Education in The Theological Perspective - Rudi Ahmad Suryadi (Al-Hayat Al-Istiqomah Foundation, 2019)
There is a differentiation between both Islamic and Western education. Western education has no conception of the will of God, the good pleasure of God, the design of human servitude to God, and let alone the understanding about life after death. Western view more striking on social interests alone (Humancentris) without trying to relate it to the Supreme Reality intervention. Education in Islamic perspective, mainly supported by theology, gave enlightenment to issues such as education. Islamic does not mean do not look optimal human capability, but in spite of this achievement of social progress as a result of the educational process remain in the corridor and the involvement of God's relationship. Islamic education, with a theological perspective presents an alternative conception of the development of an educational standpoint. Terdapat perbedaan antara pendidikan Islam dan Barat. Pendidikan Barat tidak memiliki konsepsi kehendak Tuhan, kesenangan baik Tuhan, konsepsi perbudakan manusia kepada Tuhan, dan apalagi konsepsi tentang kehidupan setelah mati. Pandangan Barat lebih mengena pada kepentingan manusia saja (Humancentris) tanpa berusaha menghubungkannya dengan intervensi Realitas Tertinggi. Pendidikan dalam pandangan Islam terutama didukung oleh teologi memberi pencerahan untuk masalah-masalah pendidikan tersebut. Islam tidak berarti tidak melihat kemampuan manusia yang optimal, tetapi terlepas dari pencapaian kemajuan manusia ini sebagai hasil dari proses pendidikan tetap berada di koridor dan keterlibatan hubungan Tuhan. Pendidikan Islam dengan perspektif teologis menghadirkan konsepsi alternatif tentang perkembangan sudut pandang pendidikan.